A. T. Mahan papers - Mahan, A. T. (Alfred Thayer), 1840-1914.
Four letters (1911-1913) by Mahan to Carter H. Fitz-Hugh concerning U.S. defense policy, the Panama Canal, and Germany's territorial conditions; letter by Mahan (1861 October 10) to C. S. Newcome from the sloop Pocahontas; photocopy of a report (1906) by Mahan on the Naval War Board of 1898 with attachments that include copies of letters to and from Adm. George Dewey and Secretary of the Navy Charles J. Bonaparte; and photocopies of excerpts from two published works on Mahan referring to the report.
Naval officer and author.
Forms part of: Naval Historical Foundation collection.
Keywords: Bonaparte, Charles J. -- 1851-1921 -- Correspondence; Dewey, George, -- 1837-1917 -- Correspondence; Fitz-Hugh, Carter H. -- Correspondence; Newcome, C. S. -- Correspondence; Naval War Board of 1898 (U.S.); Pocahontas (Screw sloop); United States. -- Navy -- Officers; Canals -- Panama; Panama Canal (Panama); Germany -- Foreign relations; United States -- Military policy; Authors; Naval officers